Respostas fisiológicas de cultivares de cana-de-açúcar submetidas à deficiência hídrica e a reidratação - Silva, Marcelo de Almeida [UNESP] (2013)
The aim of this work was to study the physiological responses of three contrasting cultivars of sugar cane subject to water stress and rewatering, The experiment was carried out in a greenhouse, where the cultivars SP83-2847, SP80-1842 and SP81-3250 were grown in pots. The first assessment was done after 85 days of planting, then two treatments were implemented, i.e. without water stress (-D) and with water stress (+D) by withholding water for 15 days and rewatering imposed for 12 days after the stress period. Cultivars SP81-3250 and SP80-1842 showed a higher decline in the Fv/Fm ratio, leaf relative water content (RWC), leaf water potential (Ψw), SPAD index and photosynthetic pigments due to water deficit. Drought caused less damage in the physiology of the variety SP83-2847, and it still showed rapid recovery during rewatering, including for the stomatal conductance (gs), so this variety had better adaptation under this condition. The traits Fv/Fm, Ψw, RWC, SPAD index and photosynthetic pigments present as potential physiological indicators in order to select tolerant sugar cane cultivars to water deficit. The trait gs is more effective in differentiating the tolerant cultivars during rewatering.